Mitochondrial dysfunction in hearing loss: Oxidative stress, autophagy and NLRP3 inflammasome - Li, Peipei; Li, Shen; Wang, Le; Li, Hongmin; Wang, Yang; Liu, Hongbing; Wang, Xin; Zhu, Xiaodan; Liu, Zhangsuo; Ye, Fanglei; Zhang, Yuan (Frontiers in Cell and Developmental Biology, 2023)
Sensorineural deafness becomes an inevitable worldwide healthy problem, yet the current curative therapy is limited. Emerging evidences demonstrate mitochondrial dysfunction plays a vital role of in the pathogenesis of deafness. Reactive oxygen species (ROS)-induced mitochondrial dysfunction combined with NLRP3 inflammasome activation is involved in cochlear damage. Autophagy not only clears up undesired proteins and damaged mitochondria (mitophagy), but also eliminate excessive ROS. Appropriate enhancement of autophagy can reduce oxidative stress, inhibit cell apoptosis, and protect auditory cells. In addition, we further discuss the interplays linking ROS generation, NLRP3 inflammasome activation, and autophagy underlying the pathogenesis of deafness, including ototoxic drugs-, noise- and aging-related hearing loss.